Leading Schools Digitally : Evaluation of the Electronic School Planning and Budgeting System (e-RKAS) in Indonesia - World Bank (World Bank, Washington, DC, 2020)
The education system under the Ministry of Education and Culture (MoEC) in Indonesia is highly decentralized. Most school costs under MoEC are covered by fiscal transfers from the centre to provincial and district levels, some of which are earmarked for education use. One such type of transfer is school operational grants, known as Bantuan Operasional Sekolah (BOS) or school operational assistance. BOS funds are managed directly by schools, which have been delegated the autonomy to receive, plan and budget, spend, administer, and report their use. Experience has shown that many schools lack the capacity to use BOS funds effectively and efficiently to deliver better learning outcomes for students, while there have been no planning systems to manage use of BOS funds towards achieving the National Education Standards (NES) for individual schools. Under the BOS program, each school is required to conduct a School Self‐Evaluation (SSE) against the NES and use the results to develop its spending plans accordingly. Every school has also been advised to develop a planning and budgeting system (Rencana Kegiatan dan Anggaran Sekolah or RKAS) to allocate and manage BOS funds. To support implementation of the RKAS, an application called the Rencana Kegiatan dan Anggaran Sekolah Berbasis Elektronik (e‐RKAS or electronic school plan) has been developed. To assess the preliminary effects of introducing different e‐RKAS applications on the role and behaviour of stakeholders, as well as challenges experienced during implementation, the World Bank conducted an evaluation of the e‐RKAS program. This report focuses on the evaluation and impact of e‐RKAS.